Proteomic Analysis of UV-B-Induced Virulence-Mutant Strains of Puccinia striiformis f. sp. tritici Based on iTRAQ Technology - Zhao, Yaqiong; Cheng, Pei; Zhang, Yuzhu; Wang, Haiguang (Frontiers in Microbiology, 2020)
The emergence of new physiological races of Puccinia striiformis f. sp. tritici (Pst) causing wheat stripe rust can lead to the loss of resistance of wheat cultivars to stripe rust, thus resulting in severe losses in wheat yield. In this study, after the germination of urediospores of three Pst strains including the original strain (CYR32, a dominant physiological race of Pst in China) and two virulence-mutant strains (CYR32-5 and CYR32-61) acquired from CYR32 via UV-B radiation, proteomic analysis based on isobaric tags for relative and absolute quantification (iTRAQ) technology was performed on the strains. A total of 2,271 proteins were identified, and 59, 74, and 64 differentially expressed proteins (DEPs) were acquired in CYR32-5 vs. CYR32, CYR32-61 vs. CYR32, and CYR32-61 vs. CYR32-5, respectively. The acquired DEPs were mainly involved in energy metabolism, carbon metabolism, and cellular substance synthesis. Furthermore, quantitative reverse transcription PCR assays were used to determine the relative expression of the 6, 7, and 1 DEPs of CYR32-5 vs. CYR32, CYR32-61 vs. CYR32, and CYR32-61 vs. CYR32-5, respectively, at the transcriptional level. The relative expression levels of one, five, and one gene, respectively, encoding the DEPs, were consistent with the corresponding protein abundance determined by iTRAQ technology. Compared with CYR32, the DEPs associated with energy metabolism and stress—including E3JWK6, F4S0Z3, and A8N2Q4—were up-regulated in the mutant strains,. The results indicated that the virulence-mutant strains CYR32-5 and CYR32-61 had more tolerance to stress than the original strain CYR32. The results obtained in this study are of great significance for exploring the virulence variation mechanisms of Pst, monitoring the changes in Pst populations, breeding new disease-resistant wheat cultivars, and managing wheat stripe rust sustainably.